2020
DOI: 10.1128/aac.01377-20
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant β-Lactam Therapy Combined with Vancomycin or Daptomycin for Methicillin-Resistant Staphylococcus aureus Bacteremia: a Systematic Review and Meta-analysis

Abstract: Infections due to methicillin-resistant Staphylococcus aureus bacteraemia (MRSAB) seriously threaten public health due to poor outcomes and high mortality. The objective of this study is to perform a systematic review and meta-analysis of the current evidence on adjuvant β-lactam (BL) therapy combined with vancomycin (VAN) or daptomycin (DAP) for MRSAB. PubMed, Embase and Cochrane Library were systematically searched for publications reporting clinical outcomes of BLs+VAN or BLs+DAP for adult patients with MRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…A recent meta-analysis of 15 studies (3 RCTs) on 2594 patients investigating the role of adjuvant beta-lactam therapy failed to demonstrate an overall benefit on mortality of combination regimens compared with DAP or VAN alone (relative risk 1.14. 95% CI 0.92–1.57), although a positive effect was apparent regarding clinical failure, recurrence or persistence of bacteremia, as well as on death rate when considering the small subgroup (three studies) of patients receiving DAP plus beta-lactam [ 40 ]. The association between DAP and a beta-lactam agent is intriguing since it might help to circumvent the emergence of strains non-susceptible to DAP and the emergence of resistance to host cationic antimicrobial peptides; by a so-called “see-saw” effect mechanism, MRSA strains might gain improved susceptibility to beta-lactams [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of 15 studies (3 RCTs) on 2594 patients investigating the role of adjuvant beta-lactam therapy failed to demonstrate an overall benefit on mortality of combination regimens compared with DAP or VAN alone (relative risk 1.14. 95% CI 0.92–1.57), although a positive effect was apparent regarding clinical failure, recurrence or persistence of bacteremia, as well as on death rate when considering the small subgroup (three studies) of patients receiving DAP plus beta-lactam [ 40 ]. The association between DAP and a beta-lactam agent is intriguing since it might help to circumvent the emergence of strains non-susceptible to DAP and the emergence of resistance to host cationic antimicrobial peptides; by a so-called “see-saw” effect mechanism, MRSA strains might gain improved susceptibility to beta-lactams [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A final score was assigned to each study after consensus between the reviewers. NOS scores can vary from 0 to 9, and studies, with an average score of ≥6 were included for this review ( Table S1 ) [ 133 ]. A meta-analysis of the studies was not performed due to a high level of heterogeneity.…”
Section: Methodsmentioning
confidence: 99%
“…Improved outcomes for patients with SAB have been sought through efforts to enhance antimicrobial efficacy by using combination antimicrobial therapy. In a previous meta-analysis of β-lactams combined with aminoglycosides, rifampicin combined with standard regimens for the treatment of SAB, β-lactams combined with vancomycin, or daptomycin in the treatment of MRSAB, it was suggested that combination therapy cannot significantly reduce the mortality of patients compared with that for monotherapy [ 17 , 18 , 36 ]. The above three meta-analyses are consistent with our results; however, owing to the poor quality and heterogeneity of the studies included in these meta-analyses, convincing clinical data are sparse.…”
Section: Discussionmentioning
confidence: 99%
“…Several efforts have been made through meta-analyses to investigate whether combination antibiotic therapy is associated with better clinical outcomes than monotherapy. However, these meta-analyses either included a small number of patients with S. aureus infections or most of the included studies were non-RCTs with large heterogeneity that affected the reliability of the results [17][18][19]. We aimed to systematically review and synthesize the published RCTs via meta-analysis methodology to examine whether combination antibiotic therapy was associated with more favourable clinical outcomes than monotherapy in patients with SAB.…”
Section: Introductionmentioning
confidence: 99%